Arduino Based Ecg & Heartbeat Monitoring Healthcare System - Noufal Qader, Noufal Younis; Khader Ahmed, Ali Mohammed; Hassan Ibrahim, Rayan Ibrahim; Al kanaan, Iyad Faza Turki (American Journal of Botany and Bioengineering, 2024)
The Arduino-based ECG and heartbeat monitoring healthcare system project aims to develop a low-cost and efficient solution for monitoring heartbeats and detecting anomalies in the ECG signal. The system uses an Arduino microcontroller and a heartbeat pulse sensor module to capture the ECG signal and gives the heart rate (BPM), which is then displayed in real-time on a ST7789 240 x 240 RGB TFT IPS LCD display module. Signal processing techniques are applied to enhance and remove noise from the ECG signal. The project has significant potential applications in the field of healthcare, including monitoring patients with heart conditions, tracking vital signs during medical procedures, and providing real-time feedback during rehabilitation programs. The low-cost nature of the project makes it an affordable option for low-income communities and developing countries.